2012
DOI: 10.1007/s10585-012-9516-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of metastatic tumor formation in vivo by a bacteriophage display-derived galectin-3 targeting peptide

Abstract: Galectin-3 (gal-3) is involved in the metastatic cascade and interacts with the cancer-associated carbohydrate, Thomsen-Freidenreich (TF) antigen during early stages of metastatic adhesion and tumor formation. Our laboratory previously utilized bacteriophage display to select a peptide, G3-C12, with high specificity and affinity for gal-3 that was able to inhibit cancer cell adhesion. We hypothesized that G3-C12 would inhibit TF/gal-3 and gal-3/gal-3 interactions in vitro and in vivo and would moderate early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…For instance, it has been shown that the LGALS3 protein, galectin-3, mediates tumor cell adhesion to the ECM (66) and promotes the dissemination of tumor cells from the primary tumor (67). Galectin-3 has also been shown to be critical for the recognition and interaction of human breast cancer cells with endothelial cells of the vasculature (68,69), and those tumor cell-endothelial cell interactions are necessary for tumor cell invasion and metastasis (70). In the later steps of metastasis, galectin-3 induces apoptosis in T cells and monocytes (65).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that the LGALS3 protein, galectin-3, mediates tumor cell adhesion to the ECM (66) and promotes the dissemination of tumor cells from the primary tumor (67). Galectin-3 has also been shown to be critical for the recognition and interaction of human breast cancer cells with endothelial cells of the vasculature (68,69), and those tumor cell-endothelial cell interactions are necessary for tumor cell invasion and metastasis (70). In the later steps of metastasis, galectin-3 induces apoptosis in T cells and monocytes (65).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that the interaction of Gal‐3 with MUC‐1 via T antigen was a central principle of metastatic cell adhesion in cancer progression . Furthermore, when using the peptide G3‐012, which has a high affinity for Gal‐3, inhibition of binding between Gal‐3 and T antigen led to a decrease in lung colonization . T antigen can also be used to detect disseminated tumor cells (DTCs) from bone marrow samples, as T antigen is co‐expressed (96%–98%) with DTCs .…”
Section: Relationship Between T Antigen and Tumor Cellsmentioning
confidence: 99%
“…57,58,62,63 It is now well established that TF ag engages a specific galectin, Galectin-3 (Gal-3), during the metastatic spread of certain TF ag -bearing tumors, and that this interaction can dictate the aggressiveness of the tumor. 55,6366 Since the majority of biologically relevant carbohydrate-protein interactions require multivalent binding for enhanced avidity 67 , many of these studies have utilized platforms where the TF ag or a TF ag mimic is displayed in multiple copies for a more potent inhibitory effect.…”
Section: Introductionmentioning
confidence: 99%